Pengaruh motivasi investasi, social media influencer Tiktok dan fomo sebagai varibel mediasi terhadap minat membeli produk saham di pasar modal pada mahasiswa FKIP UNS - Nur Rochman Saputra; Dewi Kusuma Wardani (Universitas Negeri Surabaya, 2025)
This study aims to determine (1) the effect of investment motivation on interest in buying stock products in the capital market, (2) the effect of Social media influencer Tiktok on interest in buying stock products in the capital market, (3) Fear of Missing Out (FoMO) mediates social media influencer Tiktok effect on interest in buying stock products in the capital market in FKIP UNS students. The research method used in this study is quantitative with data collection techniques using a questionnaire. The population in this study were FKIP students at Sebelas Maret University. The sampling technique used proportional stratified random sampling from 25 study programmes in FKIP UNS. The results showed that: (1) There is a positive and significant influence between investment motivation on the interest in buying shares of FKIP UNS students. (2) There is a positive and significant influence between social media influencers on the interest in buying shares of FKIP UNS students. (3) There is a positive and significant influence between FoMO mediating social media influencers on the interest in buying shares of FKIP UNS students.